Minimally Invasive off-Pump Coronary Artery Bypass Grafting of the Anterior Descending Artery: Single-Center Experience - V. N. Kolesnikov; S. T. Enginoev; A. A. Ziankou; S. S. Ekimov; M. M. Hassan; N. E. Ramazanova; M. N. Dzhambieva; G. M. Magomedov; I. I. Chernov (Креативная хирургия и онкология, 2025)
Introduction. Minimally invasive direct coronary artery bypass (MIDCAB) of the anterior descending artery provides a means to avoid artificial circulation and full sternotomy, reducing the risks of associated complications. Aim. To evaluate the short-term results of MIDCAB.Materials and methods. The retrospective study included a total of 172 patients (132 men and 40 women) who underwent surgery in 2017–2022. The mean age was 60.83 ± 8.36 years, and the BMI was 28.7 (25.8–32.3) kg/m2. The left ventricular ejection fraction amounted to 55 (49–59)%. Diabetes mellitus was diagnosed in 27.9% of patients, and atrial fibrillation was identified in 15.1% of patients. The medical history of patients included stroke (4.7%), percutaneous coronary intervention (PCI, 25.6%), and myocardial infarction (60.5%). The endpoints were in-hospital mortality and postoperative complications.Results. Hybrid interventions (MIDCAB + PCI) were performed in 4.7% of patients. The surgery took 112(90–130) minutes. Perioperative myocardial infarction and acute kidney injury occurred in 1.2% of patients. No strokes were observed. Atrial fibrillation was diagnosed in 13.4% of patients; reexploration for bleeding occurred in 2.9% of cases; postoperative wound suppuration was observed in 0.6% of patients. The in-hospital mortality amounted to 0.6%. The length of ICU stay was 22 (18–24) hours, and the inpatient stay lasted 9 (8–11) days.Discussion. MIDCAB shows good short-term results, combining the advantages of minimally invasive access and standard bypass surgery.Conclusion. MIDCAB is an effective technique to achieve revascularization of the anterior descending artery that ensures low mortality and complication rates.